IL-2, IL-6 and chitinase 3-like 2 might predict early relapse activity in multiple sclerosis - Petržalka, Marko; Meluzínová, Eva; Libertínová, Jana; Mojžišová, Hana; Hanzalová, Jitka; Ročková, Petra; Elišák, Martin; Kmetonyová, Silvia; Šanda, Jan; Sobek, Ondřej; Marusič, Petr (PloS one, 2022)
BACKGROUND: The possibility to better predict the severity of the disease in a patient newly diagnosed with multiple sclerosis would allow the treatment strategy to be personalized and lead to better clinical outcomes. Prognostic biomarkers are highly needed. OBJECTIVE: To assess the prognostic value of intrathecal IgM synthesis, cerebrospinal fluid and serum IL-2, IL-6, IL-10, chitinase 3-like 2 and neurofilament heavy chains obtained early after the onset of the disease. METHODS: 58 patients after the first manifestation of multiple sclerosis were included. After the initial diagnostic assessment including serum and cerebrospinal fluid biomarkers, all patients initiated therapy with either glatiramer acetate, teriflunomide, or interferon beta. To assess the evolution of the disease, we followed the patients clinically and with MRI for two years. RESULTS: The IL-2:IL-6 ratio (both in cerebrospinal fluid) <0.48 (p = 0.0028), IL-2 in cerebrospinal fluid ≥1.23pg/ml (p = 0.026), and chitinase 3-like 2 in cerebrospinal fluid ≥7900pg/ml (p = 0.033), as well as baseline EDSS ≥1.5 (p = 0.0481) and age <22 (p = 0.0312), proved to be independent markers associated with shorter relapse free intervals. CONCLUSION: The IL-2:IL-6 ratio, IL-2, and chitinase 3-like 2 (all in cerebrospinal fluid) might be of value as prognostic biomarkers in early phases of multiple sclerosis.
Keywords: recidiva; Interleukin-2; interleukin-2; Chronic Disease; Recurrence; chitinasy; Interleukin-6; Humans; biologické markery; roztroušená skleróza; Chitinases; lidé; Biomarkers; interleukin-6; chronická nemoc; Multiple Sclerosis